TANTANGAN GURU SEKOLAH DASAR DALAM MENGAJAR IPA TERUTAMA DALAM KETERBATASAN SARANA DAN KOMPETENSI GURU - Ayu Septiah Utami; Hazeirin Astin; Shanata Pratiwi; Melanie Cynthia Negara; Sandrina Dwi Melany; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science education (IPA) at the elementary school level plays a crucial role in shaping students' scientific thinking and basic science skills. However, the implementation of science learning at SDN 55/I Sridadi still faces numerous challenges, particularly regarding limited infrastructure and teachers' competencies. This article aims to explore in depth the obstacles encountered by teachers in teaching science and to propose strategic solutions for improving the quality of learning. The research employed a descriptive qualitative approach, with data collected through literature review and interviews with fifth-grade homeroom teachers at SDN 55/I Sridadi. The findings indicate that the main challenges faced by teachers are the lack of adequate facilities and the limited competency in teaching science effectively. The study recommends enhancing educational facilities and providing ongoing teacher training as concrete steps to overcome these obstacles.